Ownership structure and bank risk-taking in ASEAN countries: A quantile regression approach - Quang Khai Nguyen (Cogent Economics & Finance, 2020)
This study examines the effect of ownership structure on the risk-taking behavior of banks in ASEAN countries. Using a sample of 96 commercial banks in ASEAN countries from 2002 to 2018, the study demonstrates that the relationship between ownership structure and bank risk-taking behavior is correlated with the characteristics of individual banks in terms of quantile regression. First, state ownership and foreign ownership affect bank risk-taking positively in high-risk banks while negatively in low-risk banks. Second, the relationship between ownership concentration and risk-taking is negative in all distributions of bank risk. These findings suggest that appropriate ownership structure can constrain bank risk-taking activities in accordance with the level of risk of each bank.
Keywords: G21; G28; G30; G32; G33; G38; 330; bank risk-taking; ownership structure; quantile regression